تقييم دور البحث العلمي في تلبية احتياجات التنمية المستدامة (دراسة حالة مؤسسات التعليم العالي السورية_ جامعة تشرين_ كلية الاقتصاد) - طرابلسية, شيراز (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يعتبر البحث العلمي البعد الأساسي في التنمية المستدامة، وله الدور الهام في بناء المشروع القومي النهضوي وهو ليس رافدا للعملية الاقتصادية والاجتماعية فحسب بل هو في الصميم من نسيجها، لأنه صيغة التقدم التي بها تبنى الأوطان. من كل ما سبق تنبع أهمية الدراسة والتي توصلت إلى أن أسباب التأخر المحلي والعربي في مجال البحث العلمي يعود لعدم توفر المقومات العامة للبحث العلمي والتي يمكن تحديدها بما يلي: أولا: البيئة التمكينية للبحث العلمي والتي تشمل كل ما هو لازم لتنشيط وتطبيق البحث العلمي. ثانيا: العنصر البشري (الباحث) فالمؤهلات والشهادات لا تكفي لتكوين الباحث، بل يحتاج البحث العلمي إلى بناء قدرات خاصة بالبحث والى نشر ذهنية البحث العلمي بين العاملين في الوسط العلمي بشكل عام. ثالثا: الدعم المادي اللازم والذي يعد الركيزة الأساسية للبحث العلمي إلى جانب توفير الطلب على البحث العلمي، والذي يتطلب توفير النموذج التنموي على مستوى الدولة والذي يضع في خططه الاعتماد على العلم والتكنولوجيا كأداة للتنمية.Scientific Research is considered the basic dimension in the sustainable development, and it has the important role in the national upgrading project. It is not just a feeder for the economic and social process, but it is at the core of its texture because it is the formula of progress by which the home countries are built. From all the foregoing comes out the importance of the study which has concluded that the reasons of the local and Arab delay in the field of scientific research are attributed to the non-availability of the general constituents of the scientific research which can be determined by the following :First: The enabling environment of the scientific research that includes all what is necessary to activate and to apply the scientific research. Second: The human element (researcher), since the qualifications and educational degrees are not adequate to make a researcher. However, the scientific research requires the building up of special capacities in research, and also the spread of the scientific research mentality among those working in the scientific medium in general. Third: The necessary material support which is considered the essential foundation of scientific research, in addition to providing the demand on scientific research which requires providing the developmental model at the level of the Country, that includes in its plans the reliance on science and technology as a tool for development.